Plant Identification Learning Through Cooperative Script for Elementary Students - Siti Afidah (Universitas Tanjungpura, 2021)
The general research objective in this study was to find out the introduction of plants through cooperative scripts in fourth grade students at SDN (Public Elementary School) 37 Sungai Ambawang, Kuburaya Regency, and understand the names of plants easily. The research method used classroom action research (CAR). The subjects in this study were grade 4 students at 37 Sui Ambawang Elementary School, totaling 15 students. At the time of learning, the condition of the students was still lacking in understanding. The increase in knowledge where at the time of the pre-cycle of 15 students had just graduated three students with a percentage of 20%, continued to cycle 1, 11 students passed with a percentage of 73% and continued cycle II with improvements to planning and implementation that are accurate, precise and full of independence that supports and great efforts can only be said to pass 15 students with a percentage of 100%, with the Cooperative Script model, students are more receptive to learning because there is an equitable and accountable grouping and independence that empowers smaller groups